Review paperSkin care during the menopause period: noninvasive procedures of beauty studies - Herman, Joanna; Rost-Roszkowska, Magdalena; Skotnicka-Graca, Urszula (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Ageing is a resultant of two processes, including genetically encoded changes in an organism and modifications caused by a negative external environment impact. In the histological aspect, the skin ageing, due to endogenous factors and hormonal changes shows: excessive dryness, Malpighian layer thinning, microcirculation disorders, collagenic or elastin fiber degradation and simultaneous glycation, decreased speed of sebum and perspiration secretion. It is said that skin is a functional picture of the organism and endocrinological system. Any hormone concentration ups and downs may improve its appearance or significantly worsen its condition as well as it may lead to occurrence of dermatological changes. In adult women, the ageing process changes its significance step by step. Despite the passage of time, women want to feel good inside their skins. The adult skin is more requiring and it needs special care, often using a cosmetic apparatus. For better effect and permanent revitalization of the ageing skin, it is recommended to apply properly selected home-use cosmetic preparations. A holistic approach makes it possible to reach the skin density and thickness increase, wrinkles shallowing, humidity and resilience improvement and also recovery of the proper face oval.